(untitled) (Abdimas Medika, 2025)
This community service report aims to increase adolescents’ awareness and knowledge about the prevention of sexually transmitted diseases (STDs) at MAN 1 Samarinda. Sexually transmitted diseases are a significant health problem among adolescents, and an adequate understanding of prevention is essential to reduce the risk of infection. This community service activity was carried out on October 4, 2024 and included counseling, interactive discussions, and distribution of educational materials on STDs and prevention methods, including condom use and the importance of communication in relationships. The methods used were lectures, questions and answers, and demonstrations, which were attended by around 38 students. Evaluation results showed that before the activity, only 40% of students had adequate knowledge about STDs. After the activity, this figure increased to 85%. In addition, 90% of participants stated that they felt more prepared to apply the knowledge gained in their daily lives. This activity successfully increased adolescents’ understanding of the importance of STD prevention and is expected to contribute to the reduction of infection rates among adolescents. Recommendations for further programs include periodic counseling and integration of reproductive health materials in the school curriculum.